Inhibition of G Protein-Activated Inwardly Rectifying K+ Channels by the Antidepressant Paroxetine - Toru Kobayashi; Kazuo Washiyama; Kazutaka Ikeda (Elsevier, 2006)
Paroxetine is commonly used as a selective serotonin reuptake inhibitor for the treatment of depression and other psychiatric disorders. However, the molecular mechanisms of the paroxetine effects have not yet been sufficiently clarified. Using Xenopus oocyte expression assays, we investigated the effects of paroxetine on G protein-activated inwardly rectifying K+(GIRK) channels, which play an important role in reducing neuronal excitability in most brain regions and the heart rate. In oocytes injected with mRNAs for GIRK1/GIRK2, GIRK2, or GIRK1/GIRK4 subunits, paroxetine reversibly reduced inward currents through the expressed GIRK channels. The inhibition was concentration-dependent, but voltage-independent and time-independent during each voltage pulse. However, two structurally different antidepressants: milnacipran and trazodone, caused only a small inhibition of basal GIRK currents. Additionally, Kir1.1 and Kir2.1 channels were insensitive to all of the antidepressants. Furthermore, the GIRK currents induced by activation of A1 adenosine receptors or by ethanol were inhibited by extracellularly applied paroxetine in a concentration-dependent manner, but not affected by intracellularly applied paroxetine. Our results suggest that inhibition of GIRK channels by paroxetine may contribute partly to some of its therapeutic effects and adverse side effects. Keywords:: paroxetine, antidepressant, G protein-activated inwardly rectifying K+ (GIRK) channel, ethanol, Xenopus oocyte